Yeast Cytokinesis: Methods and Protocols - Sanchez-Diaz, Alberto; Perez, Pilar (Methods in molecular biology, 2016)
Time-lapse Fluorescence Microscopy Of Budding Yeast Cells -- Real-time Visualization and Quantification of Contractile Ring Proteins in Single Living Cells -- Fluorescence Recovery After Photo-bleaching (FRAP) and Fluorescence Loss in Photo-bleaching (FLIP) Experiments to Study Protein Dynamics during Budding Yeast Cell Division -- High-Speed Super Resolution Imaging of Live Fission Yeast Cells -- Monitoring Chitin Deposition during Septum Assembly in Budding Yeast -- Imaging Septum Formation by Fluorescence Microscopy -- Visualization of Cytokinesis Events in Budding Yeast by Transmission Electron Microscopy -- Visualization of Fission Yeast Cells By Transmission Electron Microscopy -- Characterization of Septin Ultrastructure in Budding Yeast Using Electron Tomography -- Isolation of Cytokinetic Actomyosin Rings from Saccharomyces cerevisiae and Schizosaccharomyces pombe -- Measurements of Myosin-II motor Activity during Cytokinesis In Fission Yeast -- In Vitro Biochemical Characterization of Cytokinesis Actin Binding Proteins -- Characterization of Cytokinetic F-BARs and other Membrane Binding Proteins -- Analysis of Three-Dimensional Structures of Exocyst Components -- Analysis of Rho-GTPase Activity during Budding-yeast Cytokinesis -- Detection of Phosphorylation Status of Cytokinetic Components -- Studying Protein-Protein Interactions in Budding Yeast Using Co-Immunoprecipitation -- Conditional Budding Yeast Mutants with Temperature-Sensitive and Auxin-Inducible Degrons for Screening Of Suppressor Genes -- Synchronization of the Budding Yeast Saccharomyces cerevisiae -- Fission Yeast Cell Cycle Synchronization Methods -- A Review of Fluorescent Proteins for Use in Yeast -- Visualisation and Image Analysis of Yeast Cells -- Toolbox for Protein Structure Prediction -- From Structure to Function. A Comprehensive Compendium of Tools to Unveil Protein Domains and Understand their Role in Cytokinesis.